DISTRICT METER AREA (DMA) PLANNING AT TAMAN KOTA RESIDENTIAL AREA, KEMBANGAN DISTRICT, JAKARTA. - Projo Susanto, Hans
The Taman Kota Housing Area is one of the clean water service areas of PT. XYZ is located in Kembangan District, West Jakarta City, Jakarta Province which has a total area of 150 ha and has a total of 5,379 clean water connections recorded since March 2021. Based on the performance audit of PT. XYZ in 2020, one of the factors that affect the performance of PT. XYZ in terms of distribution of clean water is water loss and non revenue water. The Taman Kota Housing Area has a water loss value that exceeds 20 percent (Minister of Public Works Regulation No. 20 of 2006) which is 43.7 percent obtained from data for March 2021, so efforts are needed to control the problem of the value of water loss. District Meter Area (DMA) is one of the water loss control efforts recommended by PT. XYZ by isolating the clean water network of the Taman Kota Residential Area into smaller areas. The establishment of a District Meter Area (DMA) is able to reduce water loss up to 18.08% (Susi Rahmania, 2019) and considered effective in overcoming the problem of water loss. Therefore, a District Meter Area (DMA) will be planned in the Taman Kota Residential Area. The purpose of this study is to identify and analyze the existing clean water distribution network system, design the District Meter Area (DMA), and optimize the clean water distribution network system after the District Meter Area (DMA) is formed in the Taman Kota Residential Area. The research method is carried out by simulating a clean water distribution system which will be simulated using the WATERGEMS V8i application lent by PT. XYZ. WATERGEMS V8i is used because it is easier to provide and input secondary data given by PT. XYZ as well as WATERGEMS V8i are easier to understand than other apps. In the operation of WATERGEMS V8i, the Hazen William formula will be used to calculate water loss, pressure, velocity, and flow rate in the distribution system of the Taman Kota Residential Area. After designing the District Meter Area (DMA) in the Taman Kota Residential Area, the value of water loss can be more controlled and the pressure on the clean water distribution system becomes more stable.